Hubungan Masa Kerja Dan Posisi Kerja Duduk Statis Terhadap Nyeri Upper Trapezius Pada Karyawan - Marya Mahardika Putri, Sima Asmara Dewa (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2024)
Someone whose job requires them to sit still for long periods of time is at risk of experiencing a forward head posture. Spasm, tightness, and stiffness can be caused by muscle overuse and overwork. The infraspinatus, scalenus, levator scapula and upper trapezius muscles contribute around 84% to the cause of discomfort which results in pain. The aim of this research was to determine the relationship between length of service and static sitting working position on upper trapezius muscle pain in employees at Widya Husada University, Semarang. This research uses a quantitative research strategy with analytical observation and a cross-sectional study design as the research methodology. Quota sampling procedures include three sets of criteria: acceptance, rejection, and dropout. The p value of 0.595 was obtained from statistical tests carried out on the relationship between working years and upper trapezius muscle pain. It was concluded that there was no significant relationship between the two. Respondents with more than ten years of work experience were 1.14 times more likely to experience upper trapezius muscle pain compared with those with less than ten years of work experience, as indicated by an odds ratio (OR) of 1.14 in this analysis. The correlation results between upper trapezius muscle pain and sitting for long periods of time are statistically significant (p = 0.001), these findings support the research hypothesis. An odds ratio (OR) of 6.75 was also produced by this analysis, meaning that there was a 6.75-fold increase in the likelihood of upper trapezius muscle pain in workers who required them to sit for long periods of time compared to those whose jobs did not require them to sit for long periods of time long time.